Optimal surgical management of pulmonary metastases: VATS versus thoracotomy. Issue 1 (9th August 2015) - Numan, Rachel C; Baas, Paul; Klomp, Houke M; Wouters, Michel W
Abstract : Survival benefit after pulmonary metastasectomy is under question and knowledge of functional recovery after pulmonary metastasectomy by thoracotomy and video‐assisted thoracoscopic surgery (VATS) is of great importance. We analysed prospective data of 100 patients operated for pulmonary metastasis by either VATS or thoracotomy. VATS yielded a better physical performance 1 month postoperative, shorter hospital stay, a shorter duration of chest tube drainage and epidural analgesia. We concluded that VATS is the preferable approach due to superior functional outcome.